The fast scalable sensor efficiency measure in a hybrid sensor network. (1st March 2013) - Lee, Chao–Yang; Shiu, Liang–Cheng; Lin, Fu–Tian; Yang, Chu–Sing
A Wireless Sensor Network (WSN) must maintain a favourable sensing coverage. In this work, a fast scalable efficient sensor measure is designed for selecting suitable mobile sensors for increasing the coverage ratio and network lifetime of mobile sensor networks. The algorithm, executed on each mobile sensor, is triggered by the event, and then responds to the header with the efficiency factor of the mobile sensor. The header determines which mobile sensors must move to heal the hole. Experiments indicate the superiority of the proposed algorithm in terms of average energy consumption and network lifetime.